The Effect of Letter Box Media Games in Improving the Ability to Recognise Alphabets at Risky Hidayah Islamic Kindergarten, Sukabumi Kec.Bandar Lampung - Sari, I.P.; Harianton, J; Dewantari, T (Utami Publisher, 2024)
The type of research used in this thesis is Pre-Experimental research with the aim of knowing whether or not there is an effect of using letter boxes on the ability to recognize letters of the alphabet in children aged 5-6 years at Risky Hidayah Islamic Kindergarten, Sukabumi District, Bandar Lampung. The research design used one group pretest-posttest design, which is a study that only uses 1 class as an experiment without a comparison group. The sample in this study was class B with a total of 10 students. The data collection techniques used are observation, tests and documentation.From the results of data analysis, it can be concluded that the data is normally distributed and homogeneous, the effectiveness test with the Y test shows that the experimental class has a significance value of 4.00 > 0.05 and a sig (2-tailed) value of 0.05 using the Wilcoxon test, which means Ho is rejected and Haha accepted. This can be proven that there is an influence in using letter box media on the ability to recognize letters of the alphabet in group B children at Risky Hidayah Islamic Kindergarten Bandar Lampung.